Fifty years of scientific research by The Wildfowl & Wetlands Trust - Newton, I (Wildfowl, 1996)
Effective conservation of any species depends on the sound understanding that can only come from research and monitoring. The 50th Anniversary seems an opportune time to look back over WWT's research, examine its development and the contribution it has made to the conservation of waterfowl, and also to set the main findings of this research within their wider scientific context. Together with education and conservation, research has always been one of WWT's main activities. The past 50 years have seen an enormous growth in ornithological research, both in Britain and elsewhere, as well as the growth of a thriving conservation movement and the establishment of a network of nature reserves. It is against this background that WWT's research development must be viewed.